Impedance and resistance of carbon ink during cure. Issue 3 (1st August 2016) - Samano, Anthony Ramores; Xu, Yanmeng; Harrison, David Jonathan; Hunt, Chris; Wickham, Martin; Thomas, Owen
Abstract : Purpose: The resistivity of cured conductive ink films is dependent on a wide range of process parameters. An early indication of the resistivity that is likely to result following curing can enable these parameters to be optimised and therefore improve product quality. This paper reports on the use of alternating current (AC) impedance measurement techniques on curing printed ink films, as a means of assessing the resistivity likely to be attained following the curing process. Design/methodology/approach: Impedance measurements (100 Hz to 10 MHz) were performed on curing conductive carbon ink films printed on polyethylene terephthalate (PET) substrates, during convective heat curing. A jig was designed to incorporate the test structure in an convection oven, such that the effect of cure on the structure impedance could be investigated. Findings: The initial impedance was found to decrease with increasing measurement frequency. As the ink films cured, the impedance magnitude across the 100 Hz to 10 MHz range converged with the DC resistance value. For a given ink, the ratio of initial AC impedance at 10 MHz to final cured resistance was found to be consistent, thus giving a method where final conductivity can be estimated before cure. Originality/value: Data from printed ink resistance measurements is required to ensure the optimal conductivity of printed devices. However, after the printed structures are fabricated and cured, it is too late to optimise process parameters, leading to significant wastage. AC Impedance measurement can give an indication of the final cured resistivity whilst the structure is freshly printed and still in its curing phase, enabling the printing process parameters to be adjusted to improve the resistivity of subsequently printed devices. Measuring AC impedance of printed ink structures in a production environment can therefore improve output.